Evaluation of reading pleasure character in SMPN 19 and SMP Adhyaksa 1 of Jambi City - Tanti Tanti; Dwi Agus Kurniawan; Muhammad Sofyan Zain; Febrina Rosa Winda; Rini Siski Fitriani (Program Pascasarjana Universitas Negeri Yogyakarta & HEPI, 2021)
This study was conducted to determine the reading pleasure of junior high school students through four indicators. The research was conducted with a total sample of 281 students from grades VII, VIII, and IX in junior high schools. The sampling technique used was purposive sampling. The research design used is an explanatory design. The quantitative instrument in the form of a reading pleasure instrument consists of 40 statements, while the qualitative instrument is in the form of interviews with ten students, four teachers, and two heads of the library. The data collection technique was carried out by survey (field research). The results of this study indicate that the indicators of general attitudes towards reading are on a neutral scale, the indicators of reading preferences are on a neutral scale, the indicators of the effects of reading on ability are on the agreeing scale, the indicators of students' negative views on reading are on the disagree scale. The results of interviews with the teacher can be seen that the teacher has reminded students always to read books other than in face-to-face activities in class, then the results of interviews with the head of the library can be seen that junior high school students have high enthusiasm for reading and borrowing books in the library, the results of interviews with male students and female students show that female students have better reading pleasure than male.